2016
DOI: 10.15280/jlm.2016.6.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Insecticide-Treated Net Use by Pregnant Women: Implications for Donor Organizations

Abstract: BackgroundThe World Health Organization (WHO) recommends the use of insecticide-treated nets (ITNs) for the prevention of malaria and reduction of mortality and morbidity from mosquito-borne diseases. Although many countries, including the Democratic Republic of Congo, have adopted this recommendation and distributed bed nets to their inhabitants, the percentage of the population using ITNs remains low.MethodsThis study was conducted with 400 mothers with at least one child under 5 years of age in health zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
6
1
0
Order By: Relevance
“…This study found that marital status was associated with the non-use of ITNs among pregnant women. The result is in line with two studies done in Kenya and Congo that found that pregnant women in a union are more likely to use an ITN [ 24 , 44 ]. The findings indicate that pregnant women who had never been in a union are less likely to use an ITN.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that marital status was associated with the non-use of ITNs among pregnant women. The result is in line with two studies done in Kenya and Congo that found that pregnant women in a union are more likely to use an ITN [ 24 , 44 ]. The findings indicate that pregnant women who had never been in a union are less likely to use an ITN.…”
Section: Discussionsupporting
confidence: 90%
“…Existing data indicate that utilization and ownership of ITNs has substantially improved owing to such campaigns in many countries in sub-Saharan Africa [ 19 ]. Similar findings were shown in a study conducted in the Democratic Republic of Congo, where 78.2% reported sleeping under ITNs regularly [ 20 ]. Lower rates of usage were however reported in a study conducted in Gulu district in Northern Uganda where only 35% of the pregnant women used ITNs [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…The odds of using ITN during pregnancy were 3.5 times higher among pregnant women with higher levels of education than among their counterparts. This result was consistent with findings from a meta-analysis conducted in Ghana [ 35 ], the Democratic Republic of Congo [ 34 ], and nations with a high malaria incidence [ 36 ]. The possible justification offered is that those with greater education are considered to have a high level of awareness of the value and significance of utilizing ITNs to prevent malaria [ 15 ].…”
Section: Discussionsupporting
confidence: 91%